A PHA / PVA nano-scale paper-based barrier emulsion and its preparation method and application
By preparing water-based nano-scale PHA/PVA emulsion, the environmental protection and barrier performance problems of paper-based coatings are solved, and stable barrier performance and biodegradability under high humidity are achieved, which is suitable for barrier coatings of paper-based packaging materials.
Patent Information
- Application Number
- CN202510673202.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-09-09
- Estimated Expiration
- 2045-05-23
AI Technical Summary
Existing paper-based coating technologies are non-degradable, difficult to recycle, or pose health risks. Bio-based coatings have insufficient barrier properties. The barrier properties of pure PVA coatings decrease significantly under high humidity. Pure PHA materials are hard and brittle, and it is difficult to prepare stable aqueous nanoemulsions. Existing PHA/PVA blending technologies have failed to achieve environmentally friendly preparation and application of paper-based barrier coatings.
Using water-based nano-scale PHA/PVA emulsion, the initial PHA particles are nano-sized to 100-300 nanometers through high-pressure homogenization and other methods. Combined with the hydrophilic and hydrophobic chain segment properties of PVA, a stable nano-scale emulsion is formed and coated on the surface of the paper-based material to prepare a barrier coating with excellent water vapor, oxygen and grease barrier properties.
Maintaining low water vapor and oxygen transmission rates at high humidity, improving coating flexibility, reducing the risk of cracking, achieving biodegradability and cost-effectiveness, meeting sustainable packaging needs, and meeting migration requirements for food packaging.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer materials technology, specifically to a PHA / PVA nanoscale paper-based barrier emulsion, its preparation method, and applications, particularly a barrier coating technology for paper-based packaging materials. The present invention also relates to a method for preparing the nanoscale emulsion and its application in preparing paper-based barrier materials. Background Art
[0002] With growing environmental awareness and demand for green packaging, traditional petroleum-based plastics face challenges due to their non-degradability and recycling difficulties, making biodegradable materials a research hotspot. Paper-based materials are widely used in packaging due to their renewable and biodegradable properties. However, their porous structure results in poor gas and water vapor barrier properties, and they are prone to moisture absorption in high humidity, which reduces their mechanical strength. Surface coating modification is required to improve their performance.
[0003] Existing paper-based coating technologies have significant deficiencies. Although polyethylene (PE) coatings are waterproof and heat-sealed, they are derived from petrochemical resources, are non-degradable, and are complex to recycle, increasing energy consumption and reducing fiber recovery rates. Paraffin coatings are low-cost, but have limited gas barrier properties, are prone to cracking at low temperatures or when bent, and are non-degradable. Coatings containing perfluoroalkyl and polyfluoroalkyl substances (PFAS) were once widely used in food packaging due to their excellent waterproof and oil-proof properties, but their environmental persistence and potential health risks have led to global restrictions. Bio-based coatings such as polylactic acid (PLA) are renewable, but have insufficient water vapor barrier properties, require industrial composting conditions for degradation, and have poor coating flexibility, making it difficult to meet high barrier requirements.
[0004] As a biopolyester, polyhydroxyalkanoate (PHA) is degradable in multiple environments, such as soil, water, and compost, and has certain water vapor and oxygen barrier properties. However, PHA production costs are high and processing performance is limited. For example, polyhydroxybutyrate (PHB) is hard and brittle, has a narrow processing window, and is easily thermally degraded. There are technical difficulties in preparing hydrophobic PHA into stable aqueous nanoemulsions of 100 to 300 nanometers. Traditional methods mostly produce micron-sized particles of 0.5 to 5 microns, which are prone to agglomeration and sedimentation, or require organic solvents, increasing environmental risks. Polyvinyl alcohol (PVA) has excellent film-forming properties and oxygen barrier properties under dry conditions, but its strong hydrophilicity causes the barrier properties to drop sharply at high humidity (relative humidity >60%-70%), limiting its water-resistant applications.
[0005] Existing PHA / PVA blending research mostly uses melting or organic solvent methods to prepare film or bulk materials, which makes it difficult to achieve environmentally friendly preparation of water-based nanoemulsions and application in paper-based barrier coatings.
[0006] In summary, there is an urgent need in this field for an environmentally friendly and cost-effective PHA / PVA nanoemulsion preparation technology that can convert PHA particles with an initial average particle size of 1 to 100 microns into a stable dispersion of 100 to 300 nanometers, forming a uniform and dense paper-based barrier coating with excellent water vapor, oxygen, and grease barrier properties, especially stable under high humidity, to replace traditional coatings and meet sustainable packaging needs. Summary of the Invention
[0007] The present invention provides a PHA / PVA nanoscale paper-based barrier emulsion, its preparation method, and application, which is used for paper-based barrier coatings. The emulsion has excellent water vapor, oxygen, and grease barrier properties, is particularly stable in high-humidity environments, is easy to coat and process, and is both biodegradable and potentially cost-effective.
[0008] The purpose of the present invention is to solve the following problems of existing paper-based barrier coating technology:
[0009] 1. Traditional coatings such as PE coating, paraffin and PFAS have environmental issues such as non-degradability, difficulty in recycling or health risks.
[0010] 2. Bio-based coatings such as PLA have insufficient barrier properties, and the barrier properties of pure PVA coatings decrease significantly under high humidity.
[0011] 3. Pure PHA materials are hard and brittle, difficult to process, and difficult to prepare stable aqueous nanoemulsions.
[0012] 4. Existing PHA / PVA blending technologies mostly rely on organic solvents or melt processing, and fail to achieve the environmentally friendly preparation of water-based nanoemulsions and the application of paper-based barrier coatings.
[0013] To achieve the above objectives, the present invention provides the following technical solutions:
[0014] The first aspect: PHA / PVA nano-scale paper-based barrier emulsion
[0015] The present invention provides an aqueous nano-scale emulsion comprising:
[0016] Polyhydroxyalkanoate PHA particles;
[0017] Polyvinyl alcohol PVA.
[0018] The average particle size of the PHA particles in the emulsion is 100 nm to 300 nm, preferably 150 nm to 250 nm, and the polydispersity index (PDI) of the particle size distribution is ≤ 0.3, more preferably < 0.25.
[0019] Characteristics of PHA:
[0020] PHA is selected from the group consisting of polyhydroxybutyrate PHB, poly (3-hydroxybutyrate-co-3-hydroxyvalerate) PHBV, poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) PHBHHx, poly (3-hydroxybutyrate-co-4-hydroxybutyrate) P3HB4HB or mixtures thereof.
[0021] The PHA is poly (3-hydroxybutyrate-co-3-hydroxyvalerate) PHBV, wherein the molar fraction of 3-hydroxyvalerate units is 2 mol % to 30 mol %, preferably 5 mol % to 20 mol %.
[0022] The weight average molecular weight of PHA is 100,000 to 1,000,000 g / mol.
[0023] Characteristics of PVA:
[0024] The alcoholysis degree of PVA is 75 mol % to 100 mol %, preferably 86 mol % to 90 mol % (partial alcoholysis) or 98 mol % to 99.9 mol % (complete alcoholysis).
[0025] The degree of polymerization of PVA is 300 to 2500, and preferably, a 4% by mass aqueous solution thereof has a viscosity of 3 to 75 mPa·s at 20°C.
[0026] Emulsion composition:
[0027] The weight ratio of PHA to PVA is 50:50 to 70:30, most preferably 70:30.
[0028] The total solid content of the emulsion is 30 wt % to 55 wt %, preferably 35 wt % to 50 wt %.
[0029] The viscosity of the emulsion is 100mPa·s to 2500mPa·s at 25°C, and the specific value depends on the total solid content and the specific type and amount of PVA.
[0030] Additives such as stabilizers, plasticizers, pH adjusters, defoamers, and preservatives may be included, with the total content not exceeding 10 wt% of the total solids weight. PVA itself can act as a stabilizer, providing steric hindrance or electrostatic stabilization by adsorption onto the surface of the PHA particles. In high solids concentrations, a small amount of additional nonionic surfactant or protective colloid may be added as appropriate to further enhance long-term storage stability, typically in an amount not exceeding 2% of the total solids weight. The nonionic surfactant is preferably polyoxyethylene sorbitan monooleate.
[0031] Emulsion stability:
[0032] The zeta potential is typically -30mV to -45mV, and the emulsion has good physical stability.
[0033] The emulsion showed no obvious sedimentation or stratification when left standing at room temperature for 30 days, and had good centrifugal stability.
[0034] Second aspect: preparation method
[0035] The present invention provides a method for preparing the above-mentioned PHA / PVA nanoscale paper-based barrier emulsion, comprising the following steps:
[0036] A PHA raw material having an initial average particle size of 1 to 100 microns, preferably 5 to 20 microns, is provided.
[0037] PVA is dissolved in water to prepare a PVA aqueous solution, and the dissolution temperature is 60°C to 95°C.
[0038] The PHA raw material and the PVA aqueous solution are mixed in a weight ratio of 50:50 to 70:30, and a uniform PHA / PVA mixture is formed by mechanical stirring or high-speed dispersion.
[0039] The mixture is nano-processed to reduce the average particle size of the PHA particles to 100 nm to 300 nm and PDI ≤ 0.3, thereby obtaining a nano-scale emulsion.
[0040] Nano-processing:
[0041] High pressure homogenization (HPH) is usually used, and the process parameters are:
[0042] Homogenization pressure: 50 MPa to 200 MPa, preferably 80 MPa to 180 MPa. For emulsions with higher solids content, such as close to 55%, it may be necessary to use a higher homogenization pressure or increase the number of cycles appropriately to achieve the target particle size and PDI.
[0043] Number of cycles: 1 to 10 times, preferably 3 to 7 times.
[0044] Temperature control: Material temperature is below 80°C to prevent PHA or PVA degradation.
[0045] Other optional methods include ultrasonic treatment, such as ultrasonic treatment at a frequency of not less than 20 kHz and a treatment time of 10 minutes to 60 minutes, microfluidization, high-speed shearing, or ball milling.
[0046] Additives can be added after mixing or nano-forming to optimize emulsion properties.
[0047] This method utilizes the hydrophilic and hydrophobic chain properties of PVA to adsorb on the surface of PHA particles under high shear, preventing particle agglomeration and achieving the preparation of stable nanoemulsions without the need for large amounts of surfactants.
[0048] The third aspect: application
[0049] The present invention provides the use of the aforementioned PHA / PVA nanoscale paper-based barrier emulsion in the preparation of paper-based barrier materials. The emulsion is applied to at least one surface of a paper-based material such as paper, cardboard, or molded fiber products, and forms a barrier coating upon drying.
[0050] Coating process:
[0051] Coating methods include knife coating, roller coating, spray coating, dip coating, flexographic printing, gravure printing or curtain coating.
[0052] The dry weight coating amount is 1 g / m² to 30 g / m², preferably 3 g / m² to 15 g / m², and more preferably 5 g / m².
[0053] The drying temperature is 50°C to 130°C, preferably 80°C to 110°C, and the drying time is until the coating is completely formed into a film.
[0054] The fourth aspect: paper-based barrier materials
[0055] The present invention provides a paper-based barrier material, comprising:
[0056] Paper-based substrate;
[0057] A barrier coating is applied and cured on at least one surface of a substrate, wherein the coating is derived from the above-mentioned PHA / PVA nano-emulsion.
[0058] performance:
[0059] Water vapor transmission rate (WVTR, 38°C, 90% RH) is less than 100 g / (m²·24h), preferably 45 g / (m²·24h).
[0060] Oxygen transmission rate (OTR, 23°C, 50% RH) <50 cm³ / (m²·24h·atm), preferably 8 cm³ / (m²·24h·atm).
[0061] Oil resistance (Kit test) grade ≥10.
[0062] The contact angle of the coating surface is 95° to 100°, showing excellent hydrophobicity.
[0063] The coating has good adhesion to the substrate, with no or slight peeling.
[0064] Beneficial effects
[0065] Compared with the prior art, the use of the PHA / PVA nanoscale paper-based barrier emulsion of the present invention and its preparation method and application can achieve the following significant beneficial effects:
[0066] Excellent emulsion properties: The average PHA particle size in the emulsion ranges from 100 to 300 nanometers, preferably 150 to 250 nanometers, with a PDI of less than 0.3 and a zeta potential typically between -30mV and -45mV. The emulsion is highly stable, with no noticeable sedimentation after 30 days of storage. The nanoscale particles promote uniform, dense film formation with excellent leveling, making it suitable for a variety of industrial coating processes. Even at a total solids content of up to 55%, optimized preparation processes can produce a nanoemulsion that meets requirements, reducing transportation and drying costs and improving production efficiency.
[0067] Excellent barrier properties: The coating maintains a low WVTR (45g / (m²·24h)) and OTR (8cm³ / (m²·24h·atm)) at high humidity (90% RH), outperforming pure PVA coatings (WVTR >300g / (m²·24h) at high humidity) and PE-coated paper (OTR 150cm³ / (m²·24h·atm)). PHA's hydrophobicity and nanostructure increase the tortuosity of the permeation path, significantly improving moisture resistance.
[0068] Improved physical properties: PHA and PVA blends improve coating flexibility and reduce the risk of cracking. PVA's adhesive properties ensure a strong bond between the coating and the paper base.
[0069] Environmentally friendly: The emulsion uses water as the dispersion medium and emits no volatile organic compounds. PHA and PVA are bio-based or biodegradable materials. The coating biodegrades 90% within 180 days according to EN 13432, making it easy to recycle or compost, in line with the requirements of a circular economy.
[0070] Cost-effectiveness: A 70:30 formulation and a coating weight of 5g / m² are preferred for achieving high barrier performance and reducing PHA usage. Preliminary estimates suggest a cost of $0.05 / m², making it economically competitive. High-pressure homogenization is a mature process suitable for large-scale production. Using a high-solids emulsion further reduces energy consumption and production time per unit of product.
[0071] Furthermore, the coating obtained by the present invention has the potential for application in food packaging. The barrier coating formed can be further tested to confirm compliance with food contact material regulations in specific countries or regions. Under the premise of complying with relevant migration limits, it meets the requirements of EU Regulation EU 10 / 2011 and US FDA 21 CFR 176.170, and its total migration amount should not exceed 10 mg / dm² or 60 mg / kg of food or food simulant. DETAILED DESCRIPTION
[0072] The present invention is described in detail below through specific examples, but the protection scope of the present invention is not limited to these examples.
[0073] The following are the raw materials used in the examples. The present invention is not limited to the use of these specific brands, and similar results can be expected using materials from other sources but with similar key properties:
[0074] The poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) PHA, also known as PHBH, and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) PHA, also known as PHBV, used are in the form of powder or micronized powder.
[0075] The partially alcoholyzed polyvinyl alcohol (PVA) used has an alcoholysis degree of 87 mol % to 89 mol % and a polymerization degree of 1700.
[0076] The fully alcoholyzed polyvinyl alcohol (PVA) used has an alcoholysis degree of 98 mol % to 99 mol % and a polymerization degree of 1700.
[0077] The basis weight of the unsized kraft paper substrate used was 80 g / m2.
[0078] The comparison material used is PE coated kraft paper, and its PE coating amount is 15g / ㎡.
[0079] Raw materials are shown in Table 1:
[0080]
[0081] Emulsion characterization
[0082] Dynamic light scattering (DLS) was used to determine the average particle size and particle size distribution index (PDI) of the PHA particles in the emulsion according to ISO 22412:2017. Zeta potential analysis was used to measure the particle surface charge and assess emulsion stability according to ISO 13099-2. Optimized emulsions, such as those with a PHA:PVA ratio of 70:30, typically exhibited an average particle size of approximately 150 nm at various solids contents, with PDI values ranging from 0.2 to 0.25 and zeta potentials ranging from -30 mV to -40 mV.
[0083] Formula optimization experiment
[0084] To determine the optimal weight ratio of PHA to PVA, a series of experiments were conducted to examine the effects of different ratios on key coating performance indicators, including water vapor transmission rate (WVTR), oxygen transmission rate (OTR), and water contact angle. The results are shown in Table 2 below:
[0085]
[0086] The experimental results in Table 2 show that when the weight ratio of PHA to PVA is 70:30, the coating exhibits the lowest water vapor transmission rate and oxygen transmission rate, as well as the highest contact angle, and has the best overall performance. Therefore, 70:30 is determined to be an optimal weight ratio of PHA to PVA.
[0087] Example
[0088] Example 1: Tianan PHBV / PVA 1799 high solid content nanoemulsion (PHA:PVA weight ratio is 70:30, using HPH method, homogenization pressure is 180MPa, total solid content is 40wt%)
[0089] Dissolve PVA 1799 in deionized water to prepare a 12% by weight aqueous solution. Heat to 90°C to 95°C to facilitate dissolution. Weigh 56g of Tianan Enmat Y1000P micropowder. If the raw material is granular, pre-micronize it to an initial average particle size of 5 to 20 microns. Slowly add the corresponding amount of PVA 1799 aqueous solution (corresponding to 30 parts of PVA) and adjust the total solids content to 40wt% for a total emulsion volume of 200g. Stir for 60 minutes using a high-speed stirrer to obtain a preliminary mixture. Transfer the mixture to a high-pressure homogenizer (HPH) at a homogenization pressure of 180MPa and perform five homogenization cycles, maintaining the material temperature below 75°C. This yields Emulsion 1. Dynamic light scattering (DLS) analysis of the emulsion revealed an average PHA particle size of 170nm and a PDI of 0.22. Zeta potential was measured using a Malvern Zetasizer Nano ZS at 25°C with deionized water as the dispersion medium, resulting in a value of -34 mV. The emulsion had a viscosity of 1300 mPa·s at 25°C. After standing for 30 days at 25°C, no visual separation was observed. After centrifugation at 3000 rpm for 15 minutes, the sedimentation rate was less than 5%.
[0090] Example 2: Tianan PHBV / PVA 1799 ultra-high solid content nanoemulsion (PHA to PVA weight ratio of 70:30, total solid content 55wt%)
[0091] PVA 1799 was dissolved in deionized water to prepare a 16.5% by weight aqueous solution. The total PVA content was 33 g, corresponding to 30 parts. 77 g of Tianan Enmat Y1000P micropowder (if the raw material is granular, it should be pre-micronized to an initial average particle size of 5 to 20 μm) was weighed and slowly added to the PVA 1799 aqueous solution to a total solids content of 55 wt% and a total emulsion volume of 200 g. Stir using a high-speed stirrer for 60-90 minutes. To aid dispersion and maintain fluidity at high solids content, polyoxyethylene sorbitan monooleate (Tween 80) (0.8% by weight of the total solids) was added at this stage. The mixture was transferred to a high-pressure homogenizer (HPH) at a homogenization pressure of 200 MPa and homogenized for 7-10 cycles, maintaining the material temperature below 78°C. This yielded Emulsion 2. Dynamic light scattering (DLS) characterization of the emulsion revealed an average PHA particle size of 190 nm and a PDI ≤ 0.25. Zeta potential, measured using a Malvern Zetasizer Nano ZS at 25°C with deionized water as the dispersion medium, was -32 mV. The emulsion had a viscosity of 2300 mPa·s at 25°C. After standing at 25°C for 30 days, the emulsion showed no visually discernible demixing or only minimal sedimentation. After centrifugation at 3000 rpm for 15 minutes, the sedimentation rate was <5-7%.
[0092] Example 3: Kaneka PHBH / PVA 1788 high solid content nanoemulsion (PHA:PVA weight ratio is 50:50, using HPH method, homogenization pressure is 150MPa, total solid content is 30wt%)
[0093] PVA 1788 was dissolved in deionized water to prepare a 15% by weight aqueous solution. The solution was heated until completely dissolved. 30 g of Kaneka Green Planet X151A powder (if the raw material is granular, it should be pre-micronized to an initial average particle size of 5 to 20 μm) was weighed and slowly added to the corresponding amount of the PVA 1788 aqueous solution to a total solids content of 30 wt% and a total emulsion volume of 200 g. The mixture was stirred for 60 minutes using a high-speed stirrer to obtain a preliminary mixture. The mixture was transferred to a high-pressure homogenizer (HPH) at a homogenization pressure of 150 MPa and homogenized for five cycles. The temperature was maintained below 70°C during the homogenization process using a cooling jacket, etc. This yielded Emulsion 3. Dynamic light scattering (DLS) analysis of the emulsion revealed an average PHA particle size of 190 nm and a PDI of 0.24. The zeta potential was measured using a Malvern Zetasizer Nano ZS at 25°C with deionized water as the dispersion medium, yielding a value of -32 mV. The viscosity of the emulsion is 800 mPa·s at 25°C. After standing at 25°C for 30 days, no obvious stratification is observed visually. The sedimentation rate is <5% after centrifugation at 3000 rpm for 15 minutes.
[0094] Example 4: Kaneka PHBH / PVA 1788 high solid content nanoemulsion (PHA:PVA weight ratio is 50:50, ultrasonic method, total solid content 30wt%)
[0095] A preliminary mixture of Kaneka PHBH / PVA 1788 was prepared according to the method of Example 3, with a total solids content of 30 wt%. The mixture was transferred to a container equipped with a cooling circuit and sonicated for 40 minutes using a probe-type ultrasonic processor at 500 W power, 20 kHz frequency, and a power setting of 70%. The ultrasonic treatment was performed in pulsed mode (e.g., 5 seconds on, 2 seconds off), with the temperature maintained below 60°C using a cooling water bath. This yielded Emulsion 4. Dynamic light scattering (DLS) analysis of the emulsion revealed an average PHA particle size of 230 nm and a PDI of 0.27. Zeta potential was measured using a Malvern Zetasizer Nano ZS at 25°C with deionized water as the dispersion medium, resulting in a value of -29 mV. The viscosity of the emulsion was 750 mPa·s at 25°C. After standing at 25°C for 30 days, no visual separation was observed. The sedimentation rate was <5% after centrifugation at 3000 rpm for 15 minutes.
[0096] Example 5: Tianan PHBV / PVA 1799 high solid content nanoemulsion (PHA to PVA weight ratio of 30:70, using HPH method, homogenization pressure of 160 MPa, total solid content of 35 wt%).
[0097] Dissolve PVA 1799 in deionized water to prepare a 24.5% by weight aqueous solution. Heat to 90°C to 95°C to facilitate dissolution. Weigh 21g of Tianan Enmat Y1000P micropowder. If the raw material is granular, pre-micronize it to an initial average particle size of 5 to 20 microns. Slowly add the corresponding amount of PVA 1799 aqueous solution, corresponding to 70 parts of PVA. Adjust the total solids content to 35wt% for a total emulsion volume of 200g. Stir for 60 minutes using a high-speed stirrer to obtain a preliminary mixture. Transfer the mixture to a high-pressure homogenizer (HPH) at a homogenization pressure of 160MPa and perform five homogenization cycles, maintaining the material temperature below 75°C. This yields Emulsion 5. Dynamic light scattering (DLS) analysis of the emulsion revealed an average PHA particle size of 175nm and a PDI of 0.23. Zeta potential was measured using a Malvern Zetasizer Nano ZS at 25°C with deionized water as the dispersion medium, resulting in a value of -33 mV. The emulsion had a viscosity of 1100 mPa·s at 25°C, and no visual delamination was observed after 30 days of standing at 25°C. The sedimentation rate was <5% after centrifugation at 3000 rpm for 15 minutes. The emulsion was coated on unsized kraft paper at a dry weight of 5 g / m² and dried at 80°C for 5 minutes. Coating properties: WVTR of 58 g / (m²·24h), OTR of 11 cm³ / (m²·24h·atm), oil resistance of 10, and contact angle of 96°.
[0098] Example 6: Study of different coating amounts using a high solids emulsion (based on the emulsion of Example 1, PHA:PVA ratio of 70:30, total solids content 40 wt%)
[0099] Using the same emulsion preparation method as in Example 1, an emulsion with a PHA:PVA ratio of 70:30 and a total solids content of 40 wt% was prepared. This emulsion was coated onto unsized kraft paper at dry weights of 3 g / m² and 10 g / m², respectively. After coating, the emulsion was dried in an 80°C oven for 5 minutes. With a coating weight of 3 g / m², the WVTR was 55 g / (m²·24h), the OTR was 13 cm³ / (m²·24h·atm), the oil resistance rating was 9, and the contact angle was 96°. With a coating weight of 10 g / m², the WVTR was 38 g / (m²·24h), the OTR was 6 cm³ / (m²·24h·atm), the oil resistance rating was 11, and the contact angle was 103°. The zeta potential of this emulsion (Example 1) was -34 mV. After the emulsion was left standing at 25°C for 30 days, no obvious stratification was observed visually, and the sedimentation rate was <5% after centrifugation at 3000 rpm for 15 minutes.
[0100] Coating and performance testing
[0101] The emulsions prepared in Examples 1 to 6, as well as the pure PVA 1788 solution used in Comparative Example 1, with solids contents similar to those in Example 3, were coated using an optimized coating process: a wire rod coater was applied to one surface of MM Group's IPACK STRONG PRO 80 g / m2 unsized kraft paper, controlling the dry weight coating to 5 g / m2. Example 6 was tested at its specific coating weight. The coated paper samples were dried in an oven at 80°C for 5 minutes. The resulting coated paper samples were then tested for performance along with untreated kraft paper (Comparative Example 2, MM Group IPACK STRONG PRO 80 g / m2) and Stora Enso's CKB PE 15 commercial PE-coated kraft paper (Comparative Example 3).
[0102] Test items and methods:
[0103] Coating weight: The mass per unit area of the coating after drying is calculated by weighing.
[0104] Water Vapor Transmission Rate (WVTR): Based on ASTM E96 / E96M, using the water cup method, the test conditions are 38°C, 90% RH.
[0105] Oxygen Transmission Rate (OTR): Tested in accordance with ASTM D3985 using MOCON and other instruments at 23°C and 50% RH.
[0106] Oil Resistance Grade Kit: Based on TAPPI T559 standard, use Kit test solution to test the coating's resistance to oil and grease penetration, and record the highest impermeability grade.
[0107] Adhesion evaluation: Use the tape peeling method, similar to ASTM D3359 method, to observe the coating being peeled off by the tape.
[0108] Contact angle: Use a contact angle meter to measure the static contact angle of a water drop on the coating surface.
[0109] Biodegradability test: Conducted in accordance with EN 13432. Coated paper samples were tested under standard composting conditions and their biodegradation rate was monitored over 180 days.
[0110] Comparative analysis of performance test results
[0111] Table 3 below summarizes the main performance test results of some samples:
[0112]
[0113] The test results in Table 3 are analyzed as follows:
[0114] Emulsion Stability and Particle Properties: Dynamic light scattering (DLS) analysis revealed that the average particle size of the PHA particles in the optimized PHA / PVA nanoemulsion can be precisely controlled to approximately 150 nanometers, with a PDI value of 0.2, indicating a very uniform particle size distribution. Zeta potential testing revealed that the surface charge of the emulsion particles ranged from -30mV to -40mV. This negative charge provides electrostatic repulsion, effectively preventing particle aggregation and ensuring the physical stability of the emulsion during storage and use. Stability testing further confirmed this: after 30 days at 25°C, the emulsion showed no visual separation. After centrifugation at 3000 rpm for 15 minutes, the sedimentation rate was less than 5%, demonstrating excellent centrifugal stability. Even at high solids contents (30wt% to 55wt%) as demonstrated in Examples 1-6, nanoemulsions meeting the requirements were obtained by adjusting the homogenization process parameters and PVA concentration. These properties demonstrate that the emulsion exhibits excellent leveling and coating suitability, forming a uniform, dense barrier film on paper-based materials.
[0115] Formula optimization and barrier performance improvement: The formula optimization experiment shown in Table 2 shows that the weight ratio of PHA to PVA has a significant impact on the barrier performance of the coating. When the PHA:PVA ratio is 70:30, the coating exhibits the best comprehensive performance:
[0116] Water vapor transmission rate (WVTR): 45g / (m²·24h) (38°C, 90%RH);
[0117] Oxygen transmission rate (OTR): 8cm³ / (m²·24h·atm) (23°C, 50%RH);
[0118] Contact angle: 100°, showing excellent hydrophobicity.
[0119] At this ratio, the hydrophobicity of PHA and the film-forming and oxygen barrier properties of PVA achieve an optimal balance. PHA's high hydrophobicity reduces water vapor permeation, while PVA's molecular chain structure enhances oxygen barrier properties. The two work synergistically to form a uniform, dense barrier film. This result demonstrates that a 70:30 ratio is the optimal formulation for achieving high barrier performance.
[0120] Effect of coating weight on barrier properties: Example 6 studied the effect of different coating weights on barrier properties in a PHA:PVA = 70:30 formulation (total emulsion solid content 40wt%). The results are as follows:
[0121] Coating amount 3g / m²:
[0122] WVTR is 55g / (m²·24h);
[0123] OTR is 13 cm³ / (m²·24h·atm);
[0124] Oil resistance grade is 9;
[0125] The contact angle is 96°.
[0126] Coating amount 10g / m²:
[0127] WVTR is 38g / (m²·24h);
[0128] OTR is 6 cm³ / (m²·24h·atm);
[0129] Oil resistance level is 11;
[0130] The contact angle is 103°.
[0131] Compared to a coating weight of 5 g / m² (as in Example 1, WVTR = 46 g / (m²·24h) and OTR = 8 cm³ / (m²·24h·atm)), increasing the coating weight significantly improves barrier performance and hydrophobicity. Both WVTR and OTR reach their optimum values at 10 g / m², indicating that increased coating thickness extends the permeation path for gases and water vapor, thereby enhancing the barrier effect.
[0132] High-solids emulsion coating performance: The different high-solids emulsions prepared in Examples 1 to 5, at the same coating weight of 5 g / m², exhibited excellent coating performance, as shown in Table 3. They all met the requirements of WVTR <100 g / (m²·24h) and OTR <50 cm³ / (m²·24h·atm), while maintaining good oil resistance and hydrophobicity. This demonstrates that the method of the present invention can produce high-solids nanobarrier emulsions with excellent performance.
[0133] Performance comparison with the comparative example:
[0134] The performance of the coating of the present invention is compared with that of the comparative example, taking Examples 1 and 2 as examples:
[0135] Pure PVA coating, comparative example 1:
[0136] Under high humidity conditions: WVTR>300g / (m²·24h);
[0137] Under high humidity conditions: OTR>100cm³ / (m²·24h·atm);
[0138] Contact angle = 65°.
[0139] Analysis: Pure PVA's barrier properties drop sharply due to its strong hydrophilicity under high humidity, and its moisture resistance is insufficient.
[0140] Untreated paper, comparative example 2:
[0141] WVTR>500g / (m²·24h);
[0142] OTR>10000cm³ / (m²·24h·atm);
[0143] Oil resistance level <1;
[0144] Contact angle <20°.
[0145] Analysis: The porous structure of untreated paper makes its barrier properties extremely poor and cannot meet packaging requirements.
[0146] PE coated paper, comparative example 3:
[0147] WVTR=10g / (m²·24h);
[0148] OTR=150cm³ / (m²·24h·atm);
[0149] Oil resistance level = 12;
[0150] Contact angle = 105°.
[0151] Analysis: PE coated paper performs well in terms of water vapor and grease barrier properties, but has poor oxygen barrier properties and is non-degradable.
[0152] Coating of the present invention, Example 1:
[0153] WVTR=46g / (m²·24h);
[0154] OTR=8cm³ / (m²·24h·atm);
[0155] Oil resistance level = 11;
[0156] Contact angle = 101°.
[0157] Coating of the present invention, Example 2:
[0158] WVTR=45g / (m²·24h);
[0159] OTR=7cm³ / (m²·24h·atm);
[0160] Oil resistance level = 11;
[0161] Contact angle = 102°.
[0162] Analysis: The coating of the present invention, i.e., the coating prepared by high solid emulsion, maintains excellent barrier properties even under high humidity, especially the OTR is much lower than that of PE coated paper. It is also biodegradable, taking into account both environmental protection and functionality.
[0163] Surface Properties and Adhesion: As shown in Examples 1 and 2, the surface contact angles of the coatings of the present invention reached as high as 101° to 102°, significantly higher than those of pure PVA coatings (65°) and untreated paper (<20°), demonstrating excellent hydrophobicity. This property is attributed to the hydrophobic nature of PHA and the dense coating film formed by nanoparticles. Tape peeling tests revealed excellent adhesion between the coating and the paper substrate, with minimal or no peeling. This demonstrates that the emulsion coatings prepared by the high-pressure homogenization method exhibit excellent adhesion to the substrate, meeting the durability requirements for practical applications.
[0164] Biodegradability: According to EN 13432, under standard composting conditions at 58°C, using Example 1 as a representative sample, the coating biodegraded 92% within 180 days, demonstrating its excellent biodegradability. PHA, as a biopolyester, can decompose under a variety of conditions, while PVA can also be degraded by microorganisms under specific conditions. The combination of these two makes the coating fully meet the environmentally friendly requirements of sustainable packaging, solving the problem of the non-degradability of traditional PE-coated paper.
[0165] Production Feasibility and Cost: The high-pressure homogenization process employed in this invention is a mature industrial process with a pressure range of 50-200 MPa and a cycle frequency of 1-10. The process parameters are controllable, demonstrating the potential for large-scale production. Preliminary cost estimates indicate that, based on a coating weight of 5g / m², the material cost is $0.05 / m², making it economically competitive with traditional materials such as PE-coated paper. Furthermore, the use of organic solvents is avoided, reducing environmental costs. The use of a high-solids emulsion significantly reduces the energy and time required for water evaporation, thereby lowering drying costs, improving production line output efficiency, and further enhancing overall economic benefits.
[0166] In summary, the PHA / PVA nanoscale paper-based barrier emulsion and its preparation method provided by the present invention successfully combine the hydrophobicity of PHA with the film-forming and oxygen barrier properties of PVA through nanotechnology and formulation optimization, significantly improving the overall barrier performance of paper-based materials. The emulsion has a small particle size of 150 nanometers and high stability, with a zeta potential typically between -30mV and -45mV and no delamination after 30 days. The coating performs well in high humidity, with low WVTR and OTR values, overcoming the bottleneck of pure PVA's moisture resistance. Compared with PE-coated paper, the present invention exhibits superior oxygen barrier properties and is biodegradable, with a degradation rate of 92% within 180 days. The preparation process is environmentally friendly and can produce emulsions with a high solids content of up to 55%. The cost is manageable at $0.05 / m², making it suitable for industrial production and showing great potential to replace traditional coatings and meet the needs of sustainable packaging.
[0167] The above embodiments are intended only to illustrate the technical solutions of the present invention and are not intended to limit the scope thereof. Those skilled in the art may make various modifications, equivalent substitutions, or variations to the above embodiments without departing from the principles and spirit of the present invention, and such modifications, equivalent substitutions, or variations are intended to be included within the scope of protection defined by the claims of the present invention.
Claims
1. A PHA / PVA nanoscale paper-based barrier emulsion, characterized in that: The emulsion is an aqueous emulsion composed of the following substances: Polyhydroxyalkanoate PHA particles; Polyvinyl alcohol (PVA); The average particle size of the PHA particles in the emulsion is 100 nm to 300 nm, the weight ratio of the PHA to the PVA is 30:70 to 50:50, and the polydispersity index (PDI) of the particle size distribution of the PHA particles is ≤0.3 as measured according to ISO 22412:2017. The emulsion is coated on a paper-based substrate and dried to form a film, thereby forming a barrier coating having a dry weight coating amount of 1 g / m2 to 30 g / m2. The barrier coating has a water vapor transmission rate WVTR of ≤60 g / (m2·24h) at 38°C and 90% relative humidity; and an oxygen transmission rate OTR of <12 cm³ / (m2·24h·atm) at 23°C and 50% relative humidity.
2. The emulsion according to claim 1, characterized in that The PHA is selected from polyhydroxybutyrate PHB, poly (3-hydroxybutyrate-co-3-hydroxyvalerate) PHBV, poly (3-hydroxybutyrate-co-3-hydroxyhexanoate) PHBHHx, poly (3-hydroxybutyrate-co-4-hydroxybutyrate) P3HB4HB or a mixture thereof.
3. The emulsion according to claim 1 or 2, characterized in that The alcoholysis degree of the PVA is 75 mol % to 100 mol %, and the polymerization degree thereof is 300 to 2500.
4. The emulsion according to claim 1, characterized in that The total solid content of the emulsion is 30 wt % to 55 wt %.
5. A method for preparing the PHA / PVA nanoscale paper-based barrier emulsion according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step a. Providing a polyhydroxyalkanoate PHA raw material having an initial average particle size of 1 micron to 100 microns; Step b. dissolving polyvinyl alcohol (PVA) in water to prepare a PVA aqueous solution; Step c. mixing the PHA raw material of step a with the PVA aqueous solution of step b in a weight ratio of 30:70 to 50:50 to obtain a PHA / PVA mixture; Step d. nano-processing the mixture obtained in step c, so that the average particle size of the PHA particles in the mixture is reduced to 100 nm to 300 nm and the polydispersity index PDI of the particle size distribution is ≤ 0.3, wherein the material temperature during the nano-processing is controlled at less than 80 ° C; The emulsion prepared by the method can directly form a uniform and dense barrier coating only after drying.
6. The method according to claim 5, characterized in that The nano-processing in step d is selected from high-pressure homogenization, ultrasonic treatment, microfluidization, high-speed shearing, ball milling or a combination thereof.
7. The method according to claim 6, characterized in that The nano-sizing treatment adopts high-pressure homogenization with a homogenization pressure of 50 MPa to 200 MPa, and is carried out for 1 to 10 cycles.
8. Use of the PHA / PVA nanoscale paper-based barrier emulsion according to any one of claims 1 to 4 in the preparation of a paper-based barrier material.
9. A paper-based barrier material, characterized in that: The invention comprises a paper-based substrate and a barrier coating coated and cured on at least one surface of the paper-based substrate, wherein the barrier coating is derived from the PHA / PVA nanoscale paper-based barrier emulsion according to any one of claims 1 to 4.
Citation Information
Patent Citations
Polyhydroxyalkanoate emulsion capable of forming film at low temperature as well as preparation method and application of polyhydroxyalkanoate emulsion
CN116874816A
Aqueous biopolymer dispersions
TW202212504A
Cited By
Water-based PHA (Polyhydroxyalkanoate) coating and PHA extrusion layer compounded paper-based high-barrier material as well as preparation method and application thereof
CN121738061A
Waterborne phas-based coating for paper-based high barrier materials and method of making and using the same
CN121738061B
A repulpable recycled high barrier paper tube system for expanded food packaging and method of making the same
CN122402907A
A repulpable recycled high barrier paper tube system for expanded food packaging and method of making the same
CN122402907B